Feiras agroecológicas da cidade de João Pessoa - Paraíba: caracterização de produtores e consumidores de alimentos orgânicos e sua relação com a gastronomia paraibana - Vasconcelos, Vitor Hugo Rocha de (2018)
Agroecology and gastronomy are very current issues and demonstrate that the population is increasingly aware of the benefits of consuming food without poisons, combined with gastronomic practices. This paper approaches the relationship between family farming and consumers of organic foods in three agroecological fairs in João Pessoa city, state of Paraiba, Brazil. The objective of the research was to understand the factors that influence the exhibitors / farmers and consumers of food in the agroecological fairs of the city of João Pessoa and to associate the relationship between the consumption of these foods and the regional gastronomy. It was made a qualitative-quantitative research encompassing the three agroecological fairs, composed of farmers affiliates to a single association. They were part of the research field the agroecological fairs located in the neighborhoods of Bessa (Ecosul Association), Castelo Branco (Ecovarzea Association) and the Bairro dos Estados (Association of Organic Farmers of the Zona da Mata and Agreste Paraibano) were part of the research field. For research in agroecological fairs semi-structured questionnaires were formulated for research, which were prepared for two segments: agroecological producers and consumers of agroecological fairs. There were 194 interviews, of which 46 were producers and 148 were consumers, including the three fairs. Kruskall-Wallis non-parametric tests were used for the difference between categories, and Kendall's correlation, when the data did not present normality. Among the results obtained, it was verified that the greater motivation to purchase is related to the environment and, in this sense, this motivation was expressed more intense in consumers with high level of schooling. Concerning the gastronomy, it was verified that the perception of regionality by the interviewees is not so evident, whereas of the traditional dishes from the local cuisine, only the rubacao and the capoeira chicken were mentioned. The data allowed to conclude that culinary and gastronomy allied to the agroecology are fundamental tools for a greater expansion of agroecological practices in the field in search of food sovereignty and security.